3. Determinants of buyer-seller relationships in agribusiness supply chains for dry-land farming products in Lombok Indonesia - I Gusti Lanang Parta Tanaya (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2006)
Abstrak Walaupun ada banyak cerita sukses tentang pembangunan pertanian di Indonesia tetapi belum memberikan perbaikan yang berarti buat kesejahteraan petani. Hal ini umumnya juga terjadi di pertanian lahan kering di Lombok. Banyak penelitian dan penyuluhan di wilayah ini ditekankan pada perbaikan sistem produksi dan sangat sedikit yang diarahkan untuk pengembangan rantai pasokan (supply chain). Tulisan ini menggambarkan tentang rantai pasokan agribisnis untuk hasil pertanian petani kecil di lahan kering dan menganalisis faktor yang menentukan proses rantai pasokan itu. Studi ini mengamati rantai pasokan untuk empat komoditi – jagung, kacang tanah, ubikayu dan padi. Hasil tulisan ini mengungkapkan pola hubungan antara petani dengan pelaku rantai pasokan lainnya. Abstract Although there have been a number of success stories from the agricultural development programs undertaken in Indonesia it is acknowledged that the change has not led to a significant improvement of farmers’ welfare. This is generally the case for dryland farmers in Lombok. Much of the research and extension effort in Lombok has been targeted at developing improved dryland production systems and little effort has been devoted to developing the product supply chains. This paper describes the agribusiness supply chain (SC) issues for produce from small farmers in dry land areas and analyses the factors contributing to the supply chain process. This study has looked at four product supply chains – those for maize, peanuts, cassava, and paddy. The results explore the relationships between farmers and others in the supply chain.